2008
DOI: 10.1007/s00271-008-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Emitter discharge variability of subsurface drip irrigation in uniform soils: effect on water-application uniformity

Abstract: Emitter discharge of subsurface drip irrigation (SDI) decreases as a result of the overpressure in the soil water at the discharge orifice. In this paper, the variation in dripper discharge in SDI laterals is studied. First, the emitter coefficient of flow variation CV ? was measured in laboratory experiments with drippers of 2 and 4 L/h that were laid both on the soil and beneath it. Additionally, the soil pressure coefficient of variation CV te was measured in buried emitters. Then, the irrigation uniformity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 18 publications
5
23
1
7
Order By: Relevance
“…Lamm et al (1995) demonstraram economia no uso da água, em 25%, quando utilizada a IGS comparada ao gotejamento superficial. Quando não há problemas relacionados a entupimento o uso da IGS em solos homogêneos reapresenta elevada uniformidade de aplicação de água, sendo superior à uniformidade da irrigação por gotejamento superficial (Gil et al, 2008) o que favorece o uso dos fertilizantes via fertigação (Lamm & Trooien, 2007). Outro aspecto interessante relacionado à IGS é o uso seguro de águas residuárias por evitar o contato direto com a parte aérea das plantas e com o operador.…”
Section: Introductionunclassified
“…Lamm et al (1995) demonstraram economia no uso da água, em 25%, quando utilizada a IGS comparada ao gotejamento superficial. Quando não há problemas relacionados a entupimento o uso da IGS em solos homogêneos reapresenta elevada uniformidade de aplicação de água, sendo superior à uniformidade da irrigação por gotejamento superficial (Gil et al, 2008) o que favorece o uso dos fertilizantes via fertigação (Lamm & Trooien, 2007). Outro aspecto interessante relacionado à IGS é o uso seguro de águas residuárias por evitar o contato direto com a parte aérea das plantas e com o operador.…”
Section: Introductionunclassified
“…Devido à alta uniformidade de aplicação da água proporcionada pela IGS (Gil et al, 2008) e à aplicação da água diretamente na zona radicular das cultura, o uso dos fertilizantes via fertirrigação é favorecido na IGS (Lamm & Trooien, 2003). O uso da fertirrigação possui, de modo geral, a característica de melhorar a eficiência no uso dos nutrientes, haja vista serem aplicados de maneira fracionada, conforme a marcha de absorção de nutrientes da cultura (Roberts, 2008).…”
Section: Introductionunclassified
“…1996, Lazarovitch et al 2005. However for similar flow rates and soils, these values were smaller, within an interval from 1 to 2 m, in laboratory tests since the soil structure increases the soil mechanical resistance to water pressure under field conditions (Gil et al 2008). Emitter flow reaches a permanent value coinciding with the stabilization of h s .…”
Section: Effect Of Soil On Emitter Dischargementioning
confidence: 99%
“…A good irrigation performance requires water distribution uniformities characterized by Cu > 0.9 or CV q = 0.1, and emitters with CV m < 0.10. Observations on homogenous soils in pots, have shown that the interaction between the effect of soil on emitter discharge in low infiltration soils would work as a self-regulated mechanism (Gil et al 2008). The soil overpressure would act as a regulator, and the emitters with a greater flow rate in surface irrigation would generate a higher overpressure in the soil, which would reduce the subsurface irrigation flow rate to a greater extent than in emitters with a lower flow rate.…”
Section: Water Distribution Variabilitymentioning
confidence: 99%